Social Support's Impact on Psychological Distress and Life Satisfaction among Saudi Women in Makkah City - Alharbi, Najwa Helal (Journal of Humanities & Social Sciences, 2024)
This study explores the complex relationship between psychological distress and life satisfaction among Saudi women, with a particular focus on the moderating role of social support, applying the stress process model to examine stress in a sociological context.The research adopted a social survey and gathered data through a survey that included validated measures for assessing psychological distress, life satisfaction, and social support as the primary study variables. The study involved 442 Saudi female residents of Makkah and employed multivariable regression analysis to test hypotheses.The findings indicate that psychological distress significantly diminishes life satisfaction among Saudi women, whereas higher levels of social support are associated with increased life satisfaction. However, the anticipated interaction effect of psychological distress and social support on life satisfaction was not statistically significant among Saudi women.The study advocates for further sociological research into the factors influencing subjective well-being in this demographic, suggesting an exploration of the effects of religious practices and family dynamics to better understand their roles in improving Saudi women's life satisfaction, focusing on utilizing the stress process model of sociology in analyzing these factors.
Keywords: Social support; psychological distress; life satisfaction; stress process; Saudi women